Disclosure of human immunodeficiency virus status to children: Pattern followed by parents and caregivers - Cebsile P. Dlamini; Mokgadi C. Matlakala (AOSIS, 2020)
Background: Disclosure of human immunodeficiency virus (HIV) status may be perceived as simply the process of revealing a person's HIV status, whether positive or negative. Despite the emerging evidence of the benefits of disclosure, who, when and what to disclose to a HIV-infected child remains a challenge. Aim: This article reports on the patterns of HIV status disclosure to the infected children by their parents and caregivers. Setting: The study was conducted in the outpatient clinic of one referral hospital offering comprehensive HIV care in the Lubombo region, eSwatini. Methods: A qualitative descriptive design was followed. Data were collected through semi-structured individual interviews with a purposive sample of 13 parents and caregivers whose children were on antiretroviral treatment and collecting treatment from the specific outpatient clinic. Audio recorded data were transcribed verbatim, thematic content analysis was done and used to organise and present the findings. Results: Four themes that emerged in relation to the topic of patterns of disclosure were disclosure of HIV status as a process rather than an event, a proposed person to disclose the HIV status to the child, the appropriate age to disclose HIV status to a child and type and amount of information to give in relation to the HIV status. The proposed person to disclose the HIV status to the infected child was the parent or caregiver involved as the primary carer of the child. There was no agreeable appropriate age to disclose HIV status to an infected child and the type and amount of information to disclose varied with the individuals depending on what prompted disclosure. Conclusion: Human immunodeficiency virus disclosure to children demands parents' and caregivers' participation and their knowledge of child development.